Effectiveness of a Contextualized Interactive Multimedia for Grade 8 Science Students - Cadizal, Richard; Ban, Maria Christina (International Journal of Arts, Sciences and Education, 2024)
The Computer-Assisted Instruction is undertaken widely to catch interest and to improve student’s performance. This Descriptive and True- Experimental research was anchored in determining the effects of the developed and validated Contextualized Interactive Multimedia (CIMM) to the 58 grade 8 students of Tanglag National High School in their Science subject. To determine the level of interest of the population toward Science subject, the researcher utilized a 10-item survey-questionnaire called Test of Related Science Attitude (TORSA). Additionally, a researcher-made pretest and posttest questionnaires were administered to determine the academic performance of the respondents. Findings showed that there is an increase in the academic performance and interest toward Science of the experimental group who was exposed to the CIMMs. Moreover, significant difference does not exist between the results of the posttests of both groups. However, a significant difference can be noted between the controlled and experimental groups’ attitude toward Science subject after the implementation of the intervention.